Risk of Invasive Meningococcal Disease in Men Who Have Sex with Men: Lessons Learned from an Outbreak in Germany, 2012—2013 - Hellenbrand, Wiebke; Claus, Heike; Schink, Susanne; Marcus, Ulrich; Wichmann, Ole; Vogel, Ulrich (PloS one, 2016)
We undertook investigations in response to an invasive meningococcal disease (IMD) outbreak in men who have sex with men (MSM) in Berlin 2012-2013 to better understand meningococcal transmission and IMD risk in MSM. We retrospectively searched for further IMD cases in MSM in Germany through local health departments and undertook exploratory interviews. We performed antigen sequence typing, characterized fHbp and aniA genes of strains with the outbreak finetype and reviewed epidemiologically or spatiotemporally linked cases from 2002-2014. Among the 148 IMD-cases notified from 01.01.2012-30.09.2013 in 18-59 year-old men we identified 13 MSM in 6 federal states: 11 serogroup C (MenC, all finetype C:P1.5-1,10-8:F3-6), 2 MenB. Interviews with 7 MSM revealed frequent meeting of multiple partners online or via mobile apps and illicit drug use as potential risk factors. MenC incidence was 13-fold higher in MSM than non-MSM. MenC isolates from 9/11 MSM had a novel fHbp allele 766. All C:P1.5-1,10-8:F3-6 strains from MSM versus 16/23 from non-MSM had intact aniA genes (p = 0.04). Although definitive evidence for transmission among MSM in epidemiological or spatiotemporal clusters in 2002-2014 was lacking, clusters were more frequent in men aged 20-49 years. Molecular analysis of C:P1.5-1,10-8:F3-6 strains revealed cases with intact aniA since 2007, mainly associated with fHbp361, fHbp766 and fHbp813, all involving one or more MSM. MenC incidence was elevated in MSM during the study period. Multiple casual sexual contacts and illicit drug use were common in affected MSM. In all strains from MSM we detected an intact aniA gene coding for a nitrite reductase, which permits survival in microanaerobic environments and could play a role in meningococcal transmission in MSM through urogenital colonization. Furthermore, meningococcal transmission among MSM may be sustained over large areas and thus require modified spatiotemporal scanning algorithms for timely detection and control.